Strong fluctuations in DNA Unzipping - Sitichoke Amnuanpol (Science Faculty of Chiang Mai University, 2019)
In a living cell two strands of nucleotides forming a double helix are unbound, in response to enzymatic force, to the independent strands. Such force-induced structural transformation of DNA is studied in the context of phase transition. Fluctuations around a double helix, which is the ground-state energy configuration, are so strong that the mean field description is no longer valid. Treating two strands of nucleotides as the one dimensional continuous entities interacting via a potential, the growth of the helix wavevector under recursion relations, derived by the momentum shell renormalization group, accounts for the rapidly spatial variation of two unbound strands.